2016
DOI: 10.1139/cjes-2015-0203
|View full text |Cite
|
Sign up to set email alerts
|

The two-stage Aegean extension, from localized to distributed, a result of slab rollback acceleration

Abstract: Back-arc extension in the Aegean, which was driven by slab rollback since 45 Ma, is described here for the first time in two stages. From Middle Eocene to Middle Miocene, deformation was localized leading to (i) the exhumation of high-pressure metamorphic rocks to crustal depths, (ii) the exhumation of high-temperature metamorphic rocks in core complexes, and (iii) the deposition of sedimentary basins. Since Middle Miocene, extension distributed over the whole Aegean domain controlled the deposition of onshore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
128
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(137 citation statements)
references
References 112 publications
(116 reference statements)
8
128
0
1
Order By: Relevance
“…For the purpose of this paper, the important point is that, ∼100 Myr after the first anatectic event (a time laps that encompasses the period from ∼115 to ∼70 Ma without geochronological record on the regional scale, see Sect. 2.1), the second anatectic event did not occur in a context of delamination-driven extension (Jolivet and Brun, 2010;Burg, 2011;Marchev et al, 2013;Brun et al, 2016) but in a context of crustal-scale thrusting. This attests for polycyclic orogeny in the RMC during Alpine times.…”
Section: A Major Thrusting Event During Eocene Anatexismentioning
confidence: 92%
See 2 more Smart Citations
“…For the purpose of this paper, the important point is that, ∼100 Myr after the first anatectic event (a time laps that encompasses the period from ∼115 to ∼70 Ma without geochronological record on the regional scale, see Sect. 2.1), the second anatectic event did not occur in a context of delamination-driven extension (Jolivet and Brun, 2010;Burg, 2011;Marchev et al, 2013;Brun et al, 2016) but in a context of crustal-scale thrusting. This attests for polycyclic orogeny in the RMC during Alpine times.…”
Section: A Major Thrusting Event During Eocene Anatexismentioning
confidence: 92%
“…As for the age of the shear zone, the inference that is was active during the Eocene (Barr et al, 1999) and as late as 37 Ma (Dinter, 1998;Krohe and Mposkos, 2002) relies mainly on a set of K-Ar hornblende ages between 37 and 47 Ma (Liati, 1986). Many authors implicitly consider that these K-Ar data yield only a minimum possible age of shearing, so that the NSZ can be accepted as a major SW-vergent thrust of much older age (Mesozoic or Mesozoic-Paleocene; Ricou et al, 1998;Papanikolaou and Kranis, 2004;Krenn et al, 2010;Burg, 2011;Schenker et al, 2014;Kydonakis et al, 2016;Brun et al, 2016). With regard to the age and tectonic significance of the NSZ, three studies should be considered more closely.…”
Section: What Happened During the Cenozoic?mentioning
confidence: 99%
See 1 more Smart Citation
“…The Aegean domain used to be a mountain belt (Hellenides) during the Early Cenozoic, which collapsed since the Late Eocene-Early Oligocene, in close relationship with the southwards retreat of the Hellenic trench (Jolivet and Faccenna, 2000;Jolivet and Brun, 2010;Jolivet et al, 2013;Brun et al, 2016). Since the Late Miocene, strike-slip tectonics along the North Anatolian Fault system accommodates the lateral escape of the Anatolia (Armijo et al, 1999;Faccenna et al, 2006;Hubert-Ferrari et al, 2009;Le Pichon et al, 2015).…”
Section: Tectonics and Morphologymentioning
confidence: 99%
“…Jolivet et al, 2013;Philippon et al, 2011), or normal faulting in an overall extensional regime (Gautier et al, Solid Earth Discuss., https://doi.org /10.5194/se-2017- Hinsbergen and Schmid, 2012) including vertical axis rotations in the footwall (Malandri et al, 2017). Field evidence is controversial, as there seems neither support for a major detachment (Brun et al, 2016;Jolivet et al, 2015;Philippon et al, 2014), nor is strike-slip faulting observed on Paros, where the Mid Cycladic Lineament might be exposed (Malandri et al, 2017;Walcott and White, 1998a). Additional complexity is added due to interaction of slab roll-back with westward migration of the Anatolian Plate since ~11 Ma (Jolivet et al, 2013;Ring et al, 2010).…”
Section: E-w Shorteningmentioning
confidence: 99%